(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Over the past decades, the field of medical informatics has been growing rapidly and has drawn the attention of many researchers. The digitization of different medical information, including medical history records, research papers, medical images, laboratory analysis and reports, has generated large amounts of data that need to be handled. As the rate of data acquisition is greater than the rate of data interpretation, new computational technologies are needed in order to manage the resulted repositories of medical data and to extract relevant knowledge from them. Such methods are provided by data mining techniques, which are used for discovering meaningful patterns and trends within the data and help improving various aspects of health informatics. In order to apply data mining techniques, the data needs to be cleansed and transformed, normalization being one of the most important pre-processing methods that accomplish this purpose.This paper aims to present the impact of applying different data normalization methods, on the performance obtained with the K-Nearest Neighbour algorithm on medical data sets.